(untitled) (Web of Discoveries: Journal of Analysis and Inventions, 2024)
The article discusses characteristics of globalization and what role does globalization play in international economic relations? Statistical data shows that Globalization has changed the picture of World Economy as a result of the growing scale of cross-border trade of commodities and services, exchange of currency, movement of people and flow of information.